2012
DOI: 10.4049/jimmunol.1201247
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zone B Cell Is a Major Source of Il-10 inListeria monocytogenesSusceptibility

Abstract: Rag-1-knockout (KO) mice are highly resistant to Listeria monocytogenes infection. The role played by the many Rag-1-dependent lymphocyte lineages was studied using a genetic approach in which each Rag-1-dependent lymphocyte lineage was eliminated one at a time. Only B cell-deficient Igh-KO mice displayed reduced bacterial load and improved survival upon Listeria infection. Listeria infection of Rag-1-KO and Il-10-KO hosts that had been adoptively transferred with wild-type marginal zone B (MZB) cells, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Indeed, this has been confirmed in mice infected with S. Typhimurium or L. monocytogenes 78,104,105 .…”
Section: B Cells In the Inhibition Of Antibacterial Immunitymentioning
confidence: 77%
See 2 more Smart Citations
“…Indeed, this has been confirmed in mice infected with S. Typhimurium or L. monocytogenes 78,104,105 .…”
Section: B Cells In the Inhibition Of Antibacterial Immunitymentioning
confidence: 77%
“…B cells show similar suppressive roles during L. monocytogenes infection 105 . Compared with controls, B cell-deficient mice show increased resistance to L. monocytogenes infection, as shown by their lower bacterial loads in the spleen and liver, as well as by their improved survival rates following infection 105 .…”
Section: B Cells In the Inhibition Of Antibacterial Immunitymentioning
confidence: 98%
See 1 more Smart Citation
“…MZ B cell-derived IL-10 inhibited innate immunity and increased the host's susceptibility to Listeria infection. 55 …”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…5C), it appears IL-10 has an immunosuppressive effect in both organs during severe listeriosis. It has been demonstrated that B cells are important for IL-10 production in the spleen, but not in the liver, during L. monocytogenes infection [43], suggesting that the mechanisms involved in IL-10 production are different between the organs, which may explain the liver-specific role of ASC, IL-18, and NK cells in exacerbating lethal L. monocytogenes infection. While ASC is an inflammasome adaptor, inflammasomeindependent roles of ASC have been documented in recent studies [29,44,45] Eur.…”
mentioning
confidence: 96%